Mechanically interlocked 1T/2H phases of MoS2 nanosheets for solar thermal water purification. (November 2018) - Ghim, Deoukchen; Jiang, Qisheng; Cao, SiSi; Singamaneni, Srikanth; Jun, Young-Shin
Abstract: Solar steam generation through photothermal conversion and heat localization is an emerging technology that can potentially alleviate shortages of clean water. As a two-dimensional transition-metal dichalcogenide, molybdenum disulfide (MoS2 ) has been employed for harvesting solar energy in hydrogen gas production, disinfection, and solar cells. Here, for the first time, we demonstrate that chemically exfoliated (ce) MoS2 can be a highly efficient, scalable, and environmentally benign (low toxicity) photothermal material for solar evaporators to create fresh water. Notably, the phase transition of MoS2 from 2H (trigonal prismatic coordination) to 1T (octahedral coordination) during the exfoliation process enhances the light absorption of the ce-MoS2, generating heat more effectively. Owing to the efficient photothermal conversion of ce-MoS2 nanosheets and heat localization from using bacterial nanocellulose foam as support, high solar evaporation efficiencies of ~ 76% and ~ 81% are achieved under 0.76 kW/m 2 and 5.35 kW/m 2 light intensities, respectively. In addition, the cytotoxicity of ce-MoS2 nanosheets was lower than that of graphene oxide (GO) nanosheets with a similar size, a commonly suggested material for solar steam generation, which can alleviate the potential environmental risk. These findings not only establish ce-MoS2 as a highly attractive material for solar steam generation, but also broaden the uses of ce-MoS2 to include solar harvesting applications. Graphical abstract: Chemically exfoliated (ce) MoS2 nanosheets were mechanically interlocked with bacterial nanocellulose (BNC)), enabling an effective solar thermal water purification. The phase transition from 2H to 1T during exfoliation enhanced the light absorption of ce-MoS2, increasing the solar evaporation efficiency from 59% to 76% under 0.76 kW/m 2 light intensity. Furthermore, the cytotoxicity of ce-MoS2 was lower than that of graphene oxide. These findings suggest that highly efficient, scalable, and environmentally benign ce-MoS2 nanosheets are promising for biomedical and other solar-enabled technologies, as well as for solar steam generation. fx1 Highlights: Ce-MoS2 nanosheets embedded into BNC matrix provided mechanical stability. Phase transition of MoS2 from 2H to 1T enhanced the light absorption. Ce-MoS2 /BNC bilayer structures achieved the high solar evaporation efficiency. Cell toxicity of ce-MoS2 was lower than that of GO with a similar lateral size.